Laju Dekomposisi dan Hara Tersedia dari Pangkasan Tumbuhan Bawah Perkebunan Kelapa - Oktariani, Putri; Suryawijaya, Putu Kevin; Djajakirana, Gunawan; Iskandar (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2025)
The implementation of organic farming in peatland coconut plantations faces challenges such as the low availability of natural nutrients, restrictions on the use of synthetic fertilizers and pesticides, and the demand for soil fertility conservation to ensure sustainable production. One potential solution is the utilization of undergrowth pruning, predominantly composed of Nephrolepis sp., as a source of organic nutrients.This study aimed to determine the decomposition rate and estimate the nutrient release potential from undergrowth pruning in a coconut plantation on peat soil in Riau Province, Indonesia. The litter bag method was employed with an observation period of eight weeks. Results showed that the decomposition rate of the pruned biomass reached 1.92 g per week, with a dry weight reduction of 68%. The most abundant nutrients released during decomposition were potassium (1.79%), phosphorus (0.07%), and copper (5.68 ppm). These findings suggest that undergrowth pruning has the potential to serve as an alternative nutrient source, supporting environmentally friendly coconut cultivation systems on peatlands.